Tổng hợp Mn2O3 kích thước nanomet bằng phương pháp đốt cháy gel ở nhiệt độ thấp - Đại và cộng sự, Lưu Minh (Vietnam Journal of Chemistry, 2014)
Manganese oxide power has been synthesised at low temperature (600oC) by the combustion of gel prepared from polyvinyl alcohol (PVA) and manganese nitrate. Mn2O3 characterization is examined by X-ray diffraction (XRD), thermogravimetric and differential thermal analysis (TG-DTA), scanning electron microscopy (SEM) and BET (Brunaure-Emmet-Teller) measurements. Further thermal treatment at 500 - 800oC for 2h yields the single phase Mn2O3 with average primary size < 80 nm. It specific surface area is 47 m2/g for Mn2O3.